Cross-Cultural Communication of Christian Students in Strengthening Religious Moderation in Langsa City - Muslem Ibnu; Al Mutia Gandhi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This study aims to analyse the cross-cultural communication patterns of Christian students in Langsa City and explain their contribution to strengthening religious moderation at the interpersonal level. The research uses a qualitative approach with a phenomenological design to understand the lived experiences of Christian students as a minority group in a Muslim-majority environment. Data were collected through in-depth interviews, observations, and documentation, and then analysed using Creswell's phenomenological procedures through the stages of coding, categorization, and theme development. The results show that Christian students develop three cross-cultural communication patterns: adaptive, integrative, and defensive-situational patterns. Adaptive patterns are used to reduce initial anxiety and uncertainty through the adjustment of communication styles and respect for local norms. Integrative patterns develop as more harmonious and inclusive social relationships are formed. Meanwhile, defensive-situational patterns emerge under certain conditions as a strategy to avoid conflict. This study confirms that religious moderation is a result of daily communication practices. Theoretically, this study integrates Anxiety/Uncertainty Management (AUM) with the concept of religious moderation at the micro level. In practical terms, these findings have implications for the development of an inclusive and diversity-sensitive campus environment.